PENGARUH PENANAMAN MODAL DALAM NEGERI, PENANAMAN MODAL ASING DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI SUMATERA BARAT - Nickitha Dina Fauzy; Hasdi Aimon (Universitas Negeri Padang, 2019)
This study explains to determine the effect of domestic investment, foreign investment, and labor on economic growth in West Sumatera. The data used is secondary data in the form of time series data from 1988-2018, with documentation and library study data collection techniques obtainedfrom relevant institutions and agencies. The variables used are economic growth (PDRB), domestic investment, foreign investment and labor, the research methods used are: (1) Multiple Regression Analysis (OLS), (2) Classical Assumption Test which states that: (1) investment in the country has a positive and insignificant effect on economic growth in West Sumatera. (2) foreign investment has a positive and significant effect on economic growth in West Sumatera. (3) labor force has a positive and not significant effect on economic growth in West Sumatera. So only foreign investment has a positive and significant impact on economic growth in West Sumatera.